Development and validation of a bioanalytical LC-UV method with solid-phase extraction for determination of valproic acid in saliva. - Tonikj Ribarska, Jasmina; Haxhiu, Arlinda; Sterјev, Zoran; Kiteva Trenchevska, Gordana; Shuturkova, Ljubica; Trajkovikj Jolevska, Suzana (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2012)
A bioanalytical HPLC method with UV detection for the determination of the antiepileptic drug valproic acid in human saliva has been developed and validated. Saliva represents an alternative matrix for therapeutic monitoring of antiepileptic drugs due to the increasing interest in free drug concentration. The proposed method involved solid-phase extraction for sample preparation and yielded very good mean recoveries of 99.4 % and 97.9 % for valproic acid and IS, respectively. The calibration function for valproic acid was linear over the concentration range of 1.0-50.0 μg mL⁻¹ (R² = 0.9989). Within-run and between-run precision and accuracy were studied at four concentrations and RSDs were less than 7.3 and 2.2 %, while accuracy values were higher than 96.8 and 97.5 %, respectively. The described method provides sensitivity, linearity, precision, accuracy and is suitable for analyses of valproic acid in saliva samples.
Keywords: valproic acid; saliva; solid-phase extraction; high-performance liquid chromatography; validation